Risk of Pneumonia with Inhaled Corticosteroid/ Long-Acting β2 Agonist Therapy in Chronic Obstructive Pulmonary Disease - Shahnaz Fatima, Fasiha Tariq, Muhammad Saqib Ur Rehman, Amna Khurram, Maira Bhatti, Sabeen Arjumand (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the pneumonia risk in COPD patients, which treatment is more effective to prevent patients to develop more complex situation. Method: This randomized study design was conducted from September 2022 to December 2022 and approval by the ethical committee of the Hospital was obtained. All the participants were 45 to 65 years old. Patients were receiving a combination of medicine whereas the first group had 51 patients receiving low-dose fluticasone propionate 250 µg and salmeterol 50 µg twice in a day. The second group was receiving high-dose treatment of fluticasone propionate 500 µg and salmeterol 100 µg twice a day. Clinical follow-up proceeded for complete assessment and for safety measures. It also includes vital sign measurements such as heart rate, pneumonia, bone fracture, and hematological measurement. In the case of suspected pneumonia, moderate to severe exacerbation event chest radiography was performed. For statistical analysis two software are used one is statistics 8.1 and the other is Pad prism version 5. One Way ANOVA is applied. Results: A total 110 number of patients aged 45-65 were recruited for this study. From the total of 110, eight persons are excluded due to cystic fibrosis, pulmonary fibrosis, and bronchiectasis. 102 patients are part of this study out of which 33(32.35%) were females and 70(67.64%) were males. Patients with smoking history were 40(39.21%), history of moderate and severe exacerbations were 20(19.60%) and 8(7.84%). Patients of group one who were receiving low doses of fluticasone propionate 250µg and salmeterol 50µg shows improvement in the patient condition and at the eight week of treatment dose the results are, moderate exacerbation was found in 12(23.52%) patients with 95% Cl=1.89-2.30, severe exacerbation in 6(11.76%) with 95% confidence intervals, and pneumonia in 6(11.76%) with 95% Cl=1.71-1.67.Group two follow-up also shows improvement in patients’ health status but it also increases the chances of pneumonia development. At eight week moderate exacerbation was found in 7(13.72%) patients with 95% Cl=3.00-0.34, severe exacerbation in 4(7.84%) with 95% confidence intervals 3.06-0.56, and pneumonia in 9(17.64%) with 95% Cl= 3.08-0.66. All the factor’s p-value was statistically significant. As the number of pneumonia, patients was higher in group two patients as compared to group one. Practical implication: Pneumonia is more likely to occur in patients with chronic obstructive pulmonary disease (COPD). The frequency of acute episodes of symptom exacerbation is decreased by inhaled corticosteroids. Low dose therapy is more effective than the high doses effective in patients. This research article helps to aware the society about the risk factors and their treatment. Conclusion: we concluded that COPD patients are more vulnerable to developing pneumonia even if we used the ICS therapy in combination with long-acting β2 agonist therapy. Low dose therapy is more effective than the high doses effective in our study Keywords: chronic obstructive pulmonary disease COPD, Inhaled corticosteroids (ICS), Long-acting bronchodilators